2.2 Plasma Placental Growth Factor (PlGF) in the Diagnosis of Women with Pre-Eclampsia Requiring Delivery Within 14 Days: The PELICAN Study. (26th April 2013) - Duckworth, S; Chappell, L; Shennan, A; Griffin, M; Redman, C; Seed, P
Abstract : Introduction: Evidence exists to suggest that the symptoms of pre-eclampsia are mediated by an imbalance of circulating angiogenic factors of placental origin; reduced concentrations of placental growth factor (PlGF) have been correlated with disease severity. Methods: A prospective, observational, cohort study was undertaken in seven UK maternity units. Women presenting 20 + 0 to 40 + 6 weeks gestation with suspected pre-eclampsia had serum PlGF measurement. ISSHP definitions of hypertensive disease were assigned, blinded to PlGF values. Analysis of the enrolment sample was conducted to evaluate diagnostic accuracy for pre-eclampsia requiring delivery within 14 days for very low PlGF (<12 pg/ml) and low PlGF (>12 pg/ml < 5th centile) using PlGF high (>5th centile) as referent. Results: Diagnosis of pre-eclampsia requiring delivery within 14 days using 5th centile as threshold. Conclusion: In women presenting <35 weeks' gestation with suspected pre-eclampsia, low PlGF level rules in women requiring delivery within 14 days and high PlGF rules out preterm delivery. Test performance falls off in women presenting over 35 weeks' gestational. PlGF can assist diagnosis and identify women requiring increased care.